LANGUAGE TESTING IN ENGLISH PROFICIENCY TEST (EPT): URGENTLY NEEDED OR ADMINISTRATION FORMALITY - Ihsan, Mas Darul (UICELL, 2023)
A crucial third component is added to the field of language testing or English Proficiency Test (EPT); focusing on language assessment practices, the social consequences, and implications of language testing and assessment. Aimed to know urgently needed or administration formality, compared the ideal perspective on language testing with 14-jurnals Scopus Q1. The result proposed nine (9) reasons through qualitative approach, they are: 1) language tests used for establishing social identity, 2) language tests and the realization of the enormous power to influence education, societies, and even the status of nations as a result of performances on international tests, content language link in English language proficiency (ELP) assessments: to define and operationalize the construct of academic language proficiency, and English language arts standards, 3) use of tests to facilitate the movement of populations in the new globalized structures is the use of tests to resist the movement of peoples, identity, 4) language tests is a function of the social and political roles they play and have marked social relevance in the contemporary world, 5) language tests are used throughout the world to control the entry of students into university settings where the language of instruction is not the student’s first language and to predict the student’s ability to cope with the demands of the university settings, 6) ethics in language testing is a set of principles which draws upon moral philosophy and serves to guide good professional conduct, 7) a code in language testing to provide for accountability, 8) language tests are used throughout the world to control the entry of students into university settings where the language of instruction is not the student’s first language, 9) for content-language link in content assessments: a content assessment represent the student’s content knowledge or represent ability to read, understand, and respond to questions in English. Concluded that language testing in English Proficiency Test (EPT) is still urgently needed. Keywords: Language Testing; English Proficiency Test (EPT); Urgently Needed; Administration Formality; Proposed Reason